Association of blood pressure with cause-specific mortality in Mexican adults - Tapia-Conyer, R; Alegre-Díaz, J; Gnatiuc, L; Wade, R; Ramirez-Reyes, R; Herrington, WG; Lewington, S; Clarke, R; Collins, R; Peto, R; Kuri-Morales, P; Emberson, J (American Medical Association, 2020)
Importance Elevated blood pressure is a major cause of premature death, but there is little direct evidence demonstrating this association in studies of Hispanic populations.